Information and communication technology, agricultural profitability, and child labor in rural Peru - Diether W. Beuermann (Inter-American Development Bank (IDB), 2013)
We estimate the impact of access to information and communication technology on agricultural profitability and child labor among isolated villages in rural Peru. We exploit the timing of an intervention that provided at least one public (satellite) payphone to 6,296 villages that did not previously have communication services. Using a village level panel, we show that profitability increased by 19.7 percent. Moreover, this income shock translated into a reduction in the likelihood of child market and agricultural work of 14 and nine percentage points respectively. Overall, the evidence suggests a dominant income effect in the utilization of child labor.
hdl:11319/4645
Keywords: O1; O3; Q1; 330; Information and Communication Technologies; Peru; Child Labor